2019
DOI: 10.1055/s-0039-1677745
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cancer after a Second Unprovoked Venous Thromboembolic Event

Abstract: Patients with two unprovoked venous thromboembolism (VTE) events could be at high risk for cancer diagnosis and may therefore benefit from extended cancer screening strategies. However, accurate data on the incidence of cancer in this population is lacking. In a prospective cohort study, we followed-up with all patients who experienced two unprovoked symptomatic VTE events that occurred in less than 2 years apart. We estimated the 1-year incidence rate of cancer following the second unprovoked VTE event using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The incidence of cancer in patients with VTE is up to sixfold higher when compared with a population of similar age without VTE. [1][2][3] In clinical practice, suspicion of an underlying cancer is frequently raised in patients with VTE, especially when the event is unprovoked, that is, in the absence of a trigger or identifiable VTE risk factor. 4 The 1-year incidence of a cancer diagnosis following unprovoked VTE has been reported to be 5 to 10%, with most of the cancers being diagnosed in the first 6 months after VTE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of cancer in patients with VTE is up to sixfold higher when compared with a population of similar age without VTE. [1][2][3] In clinical practice, suspicion of an underlying cancer is frequently raised in patients with VTE, especially when the event is unprovoked, that is, in the absence of a trigger or identifiable VTE risk factor. 4 The 1-year incidence of a cancer diagnosis following unprovoked VTE has been reported to be 5 to 10%, with most of the cancers being diagnosed in the first 6 months after VTE.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, Rézig et al published a prospective study of 197 patients who had recurrent unprovoked VTE that occurred within 2 years. 1 The 1-year risk of a cancer diagnosis was 36% (95% confidence interval [CI]: 20-59) in patients with VTE recurrence during anticoagulant treatment versus 5.5% (95% CI: 2.9-10) among patients with VTE recurrence after stopping anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with recurrent VTE on anticoagulation, re-screening for occult or recurrent cancer is recommended. 15…”
Section: Management Strategiesmentioning
confidence: 99%
“…In patients with recurrent VTE on anticoagulation, re-screening for occult or recurrent cancer is recommended. 15 In patients with a confirmed VTE recurrence during vitamin K antagonists (VKAs) treatment, several options to modify the anticoagulation regimen are possible and suggested in ►Table 1. After ruling out insufficient dosage and non-compliance with the previous treatment (INR values in the target range?…”
Section: Management Strategiesmentioning
confidence: 99%
“…In patients without documented cancer, clinicians/patients/policymakers may question whether a search for underlying occult cancer is warranted in those with therapeutic failure. Indeed, Rezig and colleagues recently showed that the incidence of occult cancer detection in patients with a second episode of unprovoked VTE while on anticoagulant therapy was very high with a rate of 35.8% (95% CI, 19.7-59.2%) [23]. These high rates suggest that clinicians should have a low threshold for occult cancer screening and start with history, physical and simple age appropriate screening tests to start, followed by more costly tests such as CT chest, abdomen and pelvis [24].…”
Section: Consider the Etiology Of Recurrent Vte On Anticoagulantsmentioning
confidence: 99%